Rethinking global history - Gänger, Stefanie; Osterhammel, Jürgen (Cambridge University Press, 2024)
"This collection of essays by leading global historians sheds light on the field's conceptual foundations and analytical instruments. Readers are guided to question implicit assumptions, critically assess the extant literature and reflect on the implications of history going global. This title is also available as Open Access on Cambridge Core"--